Inflammatory Microenvironment Accelerates Bone Marrow Mesenchymal Stem Cell Aging - Peng, Xin; Zhou, Xin; Yin, Ying; Luo, Beibei; Liu, Yang; Yang, Cheng (Frontiers in Bioengineering and Biotechnology, 2022)
MSC senescence is considered a contributing factor in aging-related diseases. We investigated the influence of the inflammatory microenvironment on bone marrow mesenchymal stem cells (BMSCs) under aging conditions and the underlying mechanism to provide new ideas for stem cell therapy for age-related osteoporosis. BMSCs were cultured until passage 3 (P3) (young group) and passage 10 (P10) (aging group) in vitro. The supernatant was collected as conditioned medium (CM). Young BMSCs were cultured in the CM of P3 or P10 cells. The effects of CM from different groups on the aging and stemness of young BMSCs were examined. Quantibody® mouse inflammation array on serum extracts from young (aged 8 weeks) and old (aged 78 weeks) mice was performed and differentially expressed factors were screened out. We discovered that CM from senescent MSCs changed the physiology of young BMSCs. Systemic inflammatory microenvironments changed with age in mice. In particular, the proinflammatory cytokine IL-6 increased and the anti-inflammatory cytokine IL-10 decreased. The underlying mechanism was investigated by GO and KEGG analyses, and there was a change in the JAK-STAT signaling pathway, which is closely related to IL-6 and IL-10. Collectively, our results demonstrated that the age-related inflammatory microenvironment has a significant effect on the biological functions of BMSCs. Targeted reversal of this inflammatory environment may provide a new strategy for stem cell therapy to treat aging-related skeletal diseases.